Characterization of multiple type-VI secretion system (T6SS) VgrG proteins in the pathogenicity and antibacterial activity of porcine extra-intestinal pathogenic Escherichia coli. Issue 1 (1st January 2019) - Zong, Bingbing; Zhang, Yanyan; Wang, Xiangru; Liu, Manli; Zhang, Tongchao; Zhu, Yongwei; Zheng, Yucheng; Hu, Linlin; Li, Pei; Chen, Huanchun; Tan, Chen
ABSTRACT: Porcine extra-intestinal pathogenic Escherichia coli (ExPEC) causes great economic losses to the pig industry and poses a serious threat to public health worldwide. Some secreted virulence factors have been reported to be involved in the pathogenicity of the infection caused by ExPEC. Type-VI secretion system (T6SS) is discovered in many Gram-negative bacteria and contributes to the virulence of pathogenic bacteria. Valine-glycine repeat protein G (VgrG) has been reported as an important component of the functional T6SS. In our previous studies, a functional T6SS was identified in porcine ExPEC strain PCN033. Further analysis of the PCN033 genome identified two putative vgrG s genes ( vgrG1 and 0248 ) located inside T6SS cluster and another two ( vgrG2 and 1588 ) outside it. This study determined the function of the four putative VgrG proteins by constructing a series of mutants and complemented strains. In vitro, the VgrG1 protein was observed to be involved in the antibacterial ability and the interactions with cells. The animal model experiment showed that the deletion of vgrG1 significantly led to the decrease in the multiplication capacity of PCN033. However, the deletion of 0248 and/or the deletion of vgrG2 and 1588 had no effect on the pathogenicity of PCN033. The study of four putative VgrGs in PCN033 indicated that only VgrG1 plays an important role in the interaction between PCN033 and other bacteria or host cells. This study can provide a novel perspective to the pathogenesis of PCN033 and lay the foundation for discovering potential T6SS effectors.